The Effect of Citronella Oil and Sesame Oil Emulsion Coating on The Quality and Storability of Mangoes (Mangifera Indica L.) - Taufik Rahman; Tri Suwandi; Rena Adelia Suryani; Anisa Maharani; Chairani Azahra; Gunawan; Lu’lu’ Lathifatuzzakiyyah; N Sarah Sri Wahyuni; Nurul Annisa (Jurusan Biologi Universitas Negeri Makassar, 2023)
One of the most promising agricultural commodities is the cultivation of mangoes. One way that can be used tomaintain the quality and freshness of the fruit in a simple way is to do an emulsion coating. The purpose of thisresearch was to determine the effect of citronella oil and sesame oil emulsion coating on the quality and storabilityof mango (Mangifera indica L.). The method used in this study was a Completely Randomized Design (CRD)with two factorial treatments and controls. The first factor was citronella oil under a concentration of 0.5% and1%. The second factor is sesame oil under a concentration of 0.5% and 1%. The two oils were combined in theemulsion into three treatment combinations, namely S0W2, S2W0, and S1W1. The parameters measured in theobservations were hardness, damage, and glucose levels in the fruit. The results showed that the level of hardnessof mangoes decreased in the four treatments. Then it was found that there was an effect of delaying the maturityof the fruit with the S1W1 treatment because it was not damaged like the other treatments. While glucose levelsin the fruit have increased due to the ripening process. Coating treatment with a ratio of citronella oil concentrationof 0.5% to 0.5% sesame oil is the most effective treatment combination in maintaining quality and shelf lifebecause this treatment can delay damage to mangoes.